A new flood risk assessment framework for evaluating the effectiveness of policies to improve urban flood resilience. Issue 5 (28th May 2018) - Hammond, Michael; Chen, Albert S.; Batica, Jelena; Butler, David; Djordjević, Slobodan; Gourbesville, Philippe; Manojlović, Nataša; Mark, Ole; Veerbeek, William
ABSTRACT: To better understand the impacts of flooding such that authorities can plan for adapting measures to cope with future scenarios, we have developed a modified Drivers-Pressures-State-Impact-Response (DPSIR) framework to allow policy makers to evaluate strategies for improving flood resilience in cities. We showed that this framework proved an effective approach to assessing and improving urban flood resilience, albeit with some limitations. This framework has difficulties in capturing all the important relationships in cities, especially with regards to feedbacks. There is therefore a need to develop improved techniques for understanding components and their relationships. While this research showed that risk assessment is possible even at the mega-city scale, new techniques will support advances in this field. Finally, a chain of models engenders uncertainties. However, the resilience approach promoted in this research, is an effective manner to work with uncertainty by providing the capacity to cope and respond to multiple scenarios.